Thyroid functions and levels of some trace elements in children with beta-thalassemia major - Mohamed S Zaghlol; Mohamed T Al-Sayed; Mohamed M.S Yonis; Ahmed Q Mohamed (Wolters Kluwer Medknow Publications, 2019)
Background High plasma iron in β-thalassemia major (BTM) leads to enhanced generation of reactive oxygen species, oxidative stress, and endocrine disorders. We aimed to assess thyroid function and trace elements [copper (Cu) and zinc (Zn)] in patients of BTM and to evaluate the relation, if any, of thyroid function with iron store in the form of ferritin levels. Patients and methods A total of 30 children with BTM and 30 healthy controls were enrolled and interviewed at the Al-Azhar University. Complete blood count, random blood sugar, liver enzymes, and creatinine were measured in all participants. Iron level, total iron-binding capacity, ferritin level, Zn level, and Cu level in sera were determined. Thyroid function was also assessed by evaluating free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone (TSH) levels. Results There were significantly increased serum iron, ferritin, Cu, and Zn levels, whereas total iron-binding capacity was depleted in patients with BTM as compared with healthy controls. There were significant positive correlations between ferritin level and both serum Cu and Zn (r=0.536 and 0.513, respectively), with P value less than 0.05. Moreover, there were significant positive correlations between TSH level and both serum Cu and Zn (r=0.416 and 0.355, respectively), with P value less than 0.05. Thyroid function represented by FT3, FT4, and TSH did not correlate with serum ferritin level. Conclusion Careful monitoring of ferritin, Cu, Zn, TSH, FT4, and FT3 levels at regular intervals is recommended for early diagnosis of thyroid dysfunctions in patients with BTM.